Activities in The MTSN 6 Banjar Darussalam Martapura School Environment Based On Religious Values - Maulana, Muhammad; Rajiani, Ismi; Rusmaniah, Rusmaniah; Triyono, Sigit; Syaharuddin, Syaharuddin (The Kalimantan Social Studies Journal, 2024)
The very rapid progress of science and technology that is not balanced with the provision of religious education materials in schools can reduce the religious values that exist within students. In this regard, the presence of madrasa schools has become one of the educational institutions that has a strong connection with religion. This is because the content of religious values receives a strong emphasis on forming the character and personality of students in accordance with the values of religious teachings provided through activities in the madrasah school environment. The purpose of this writing is to determine the religious values in activities within the MTsN 6 Banjar Darussalam Martapura school environment. The research taken uses qualitative research methods with a descriptive approach. The data collection technique uses observation to systematically observe and record activities in the school environment based on religious values, interviews are conducted to obtain data directly with informants, as well as documentation. Data analysis uses data reduction, data presentation, and conclusions from the data obtained. Validity of research data by extending observation, triangulation, and conducting member checks. The results of this research are that daily activities in the MTsN 6 Banjar school environment are based on religious values, namely learning (moral beliefs, al-Quran hadith, fiqih), intracurricular (greetings & salim, recitation of the Al-Quran tadarus, and congregational prayers), extracurricular (maulid habsyi and hadrah). The conclusions from the activities in the MTsN 6 Banjar environment include religious values such as worship, the spirit of jihad, trust and sincerity, morals and discipline, example.